Casting process of crankshaft for scroll air conditioner compressor
Through the annealing, quenching, tempering treatment and wear-resistant and corrosion-resistant coating spraying process of scroll air conditioning compressor, the problems of crankshaft wear and insufficient service life are solved, and the wear and corrosion resistance of crankshaft is significantly improved. , extends service life and improves sealing performance.
Patent Information
- Application Number
- CN202411248642.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The crankshafts for existing air-conditioning compressors are prone to wear during use, resulting in the compressor failure and insufficient wear resistance and service life.
A crankshaft casting process for scroll air conditioning compressors is adopted, including heating cold heading steel to a molten state and pouring it into a mold for cooling and molding, performing annealing, quenching and tempering treatment, and spraying wear-resistant and corrosion-resistant coating on the surface. Dry by laser drying.
Improve the strength and toughness of the crankshaft through quenching and tempering treatments and extend the service life; wear-resistant and corrosion-resistant coatings significantly improve the wear and corrosion resistance of the crankshaft, reduce friction wear and environmental erosion, and multi-step polishing treatment improves the surface finish and Sealing performance and strict heat treatment control the stability of the crankshaft structure.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of crankshaft casting and relates to a casting process for a crankshaft for a scroll air-conditioning compressor. Background Art
[0002] An air-conditioning compressor is a driven fluid machine that boosts low-pressure refrigerant gas to high pressure. The air-conditioning compressor is the heart of the refrigeration system. Scroll air-conditioning compressors are widely used in household air conditioners. When the compressor is running, a crankshaft is required, and the crankshaft is the power transmission component of the piston compressor, which can provide a stable force transmission effect for the compressor. However, the existing crankshafts for air conditioners have some shortcomings during use. For example, after long-term use, wear will occur, which will cause the compressor to fail. Summary of the invention
[0003] The object of the present invention is to provide a casting process for a crankshaft for a scroll air-conditioning compressor, which has the characteristics of wear resistance and long service life.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A casting process for a crankshaft for a scroll air-conditioning compressor, the specific process of the crankshaft casting process is as follows:
[0006] S1: heating the cold heading steel to 1500°C to make the cold heading steel molten;
[0007] S2: pouring the molten cold heading steel into the mold, cooling and solidifying it to obtain a crankshaft blank;
[0008] S3: heating the crankshaft blank to 200-300° C. for 2-3 hours, performing annealing treatment, and cooling to room temperature;
[0009] S4: performing surface polishing on the annealed crankshaft blank by using a 500-mesh elastic module at 0.3-0.5 MPa for 0.5-1 h, and then using a 1000-mesh elastic module at 0.5 MPa for 0.5 h;
[0010] S5: heating the polished crankshaft blank to 830-920° C. for quenching, with a constant temperature treatment time of 1-2 hours, placing it in cooling water to quickly cool it down, and after cooling, blowing it with 70° C. nitrogen until the surface of the crankshaft blank is dry;
[0011] S6: heating the crankshaft blank after quenching to 150-200° C. for tempering, with a constant temperature treatment time of 1-2 hours, and then evenly spraying nitrogen on the surface of the crankshaft blank and slowly cooling it to room temperature;
[0012] S7: spraying a layer of wear-resistant and corrosion-resistant coating on the surface of the crankshaft blank after the tempering treatment, and then drying it by a laser drying method to obtain the crankshaft;
[0013] The preparation method of the coating used for the wear-resistant and corrosion-resistant coating is as follows:
[0014] S71: Silicon carbide and titanium nitride are mixed in a mass ratio of 1:(1-3), and ground in a ball mill at a rotation speed of 400 r / min for 0.5 h to obtain a mixture A;
[0015] S72: Heat the polyurethane resin to 170°C to make the polyurethane resin in a molten state, add 5-10wt% of mixture A, 2-4wt% of cobalt oxide, 1-2wt% of rhodium oxide, 0.5-1wt% of dispersant, and 0.5-1wt% of curing agent, stir at a speed of 150-200r / min for 1-2h, cool to room temperature, and obtain the coating used for the wear-resistant and corrosion-resistant coating.
[0016] Furthermore, the cold heading steel in S1 is ML20.
[0017] Furthermore, the purge flow rate of nitrogen in S5 is 10 m / s.
[0018] Furthermore, the spraying flow rate of nitrogen in S6 is 2.5m 3 / min, the pressure is 0.5MPa.
[0019] Furthermore, the cooling rate in S6 is 3°C / min.
[0020] Furthermore, the spraying parameters in S7 are spraying distance 100 mm and spraying rate 60 mm / s.
[0021] Furthermore, the parameters of the laser drying in S7 are: laser power 260-300 W, temperature 50-60° C., and irradiation time 20-30 min.
[0022] Furthermore, the particle size of the mixture A obtained by grinding in S71 is 200 mesh.
[0023] Furthermore, the dispersant in S72 is polyethylene glycol, and the number average molecular weight is 800-2000.
[0024] Furthermore, the curing agent in S72 is one of diisocyanate and triisocyanate.
[0025] The present invention achieves a good balance between strength and toughness of the crankshaft through quenching and tempering treatment, is able to withstand high loads and alternating stresses, and extends the service life of the crankshaft; the wear-resistant and corrosion-resistant coating sprayed on the surface significantly improves the wear resistance of the crankshaft, reduces performance degradation and failures caused by friction and wear, and the wear-resistant and corrosion-resistant coating also has a certain corrosion resistance, which can protect the crankshaft from erosion by environmental factors; after multiple steps of polishing treatment, the surface finish of the crankshaft is significantly improved, which is beneficial to reducing friction resistance and improving sealing performance; strict heat treatment process controls the organizational structure of the crankshaft, ensures its dimensional stability, and reduces dimensional changes caused by temperature changes.
[0026] During the casting process, the cold heading steel is first completely melted to facilitate subsequent casting and molding. The high temperature allows the atoms inside the cold heading steel to obtain sufficient energy, breaking the original crystal structure and forming liquid metal, which is convenient for filling the complex shape in the mold and forming the basic shape of the crankshaft blank, laying the foundation for subsequent processing. The liquid metal cools and solidifies in the mold and forms the crankshaft blank according to the shape of the mold. In this process, the metal atoms are rearranged and combined to form a new crystal structure.
[0027] Annealing treatment can eliminate casting stress and improve the metal structure, thereby increasing the plasticity and toughness of the crankshaft; heating at a lower temperature for a long time allows the atoms inside the crankshaft enough time to diffuse and rearrange, eliminating the internal stress and structural defects generated during the casting process.
[0028] Surface polishing can improve the smoothness and flatness of the crankshaft surface, reduce friction resistance and improve sealing performance. Using elastic modules with different mesh sizes to grind and polish the crankshaft surface under a specific pressure can effectively remove the rough layer and tiny defects on the surface and make the surface smoother.
[0029] The hardness and strength of the crankshaft are significantly improved through quenching treatment while maintaining a certain toughness. The crankshaft is heated to a high temperature and then rapidly cooled, causing the internal structure of the crankshaft to undergo a martensitic transformation to form a high-hardness martensitic structure. At the same time, due to rapid cooling, part of the austenitic structure is retained, thereby maintaining a certain toughness.
[0030] Tempering treatment can eliminate quenching stress, stabilize the organizational structure, and further improve the toughness and comprehensive mechanical properties of the crankshaft. The quenched crankshaft is heated and kept warm at a lower temperature to decompose and recrystallize the martensite structure to form tempered troostite or tempered troostite, which have higher toughness and good comprehensive mechanical properties.
[0031] By spraying a layer of wear-resistant and moisture-proof coating material on the crankshaft surface, a protective layer is formed to further improve the wear resistance and corrosion resistance of the crankshaft and extend its service life. This protective layer can isolate the crankshaft from contact with corrosive media in the environment, while reducing performance degradation and failures caused by friction and wear. The laser drying method can ensure that the coating dries quickly and adheres firmly to the crankshaft surface.
[0032] Silicon carbide and titanium nitride in the coating are hard ceramic materials with extremely high hardness and wear resistance. Their uniform distribution in the coating significantly improves the wear resistance of the coating and can effectively resist mechanical wear and scratches. Polyurethane resin, as a matrix material, has good sealing and moisture resistance. It can form a dense protective film that effectively isolates the penetration of water and moisture and protects the substrate from the influence and corrosion of a humid environment.
[0033] The cobalt oxide in the coating can act as a catalyst in the reaction to promote the cross-linking reaction of the polyurethane resin, which helps the coating to form a more stable and dense structure during the curing process, thereby improving the wear resistance and moisture resistance of the coating; rhodium oxide has excellent dispersibility, which helps the mixture A and other additives to be evenly dispersed in the polyurethane resin. Good dispersibility can ensure the uniformity of the coating performance and reduce the performance degradation caused by local agglomeration; in addition, rhodium oxide can also stabilize the particles of the mixture A through its surface properties to prevent them from agglomerating during the coating preparation process. Rhodium oxide reacts with the polyurethane resin or certain components in the mixture A to form chemical bonds or strong interactions. This interfacial reaction helps to enhance the internal bonding force of the coating and further improve the bonding strength between the coating and the substrate.
[0034] The addition of cobalt oxide and rhodium oxide may improve the interfacial bonding between mixture A (silicon carbide and titanium nitride) and polyurethane resin. These oxide particles may act as a "bridge" to tightly bind the hard ceramic particles (silicon carbide and titanium nitride) to the polymer matrix (polyurethane resin) through physical and chemical effects (such as adsorption, chemical bonding, etc.). This enhanced interfacial bonding helps to improve the overall strength and wear resistance of the coating.
[0035] Cobalt oxide and rhodium oxide can promote the curing reaction of polyurethane resin, help form a more stable and dense coating structure, thereby enhancing the adhesion between the coating and the substrate; cobalt oxide and rhodium oxide themselves have high hardness. When they are evenly dispersed in the polyurethane resin, they can increase the overall hardness of the coating. The increase in hardness helps the coating resist wear and peeling caused by external mechanical forces, thereby enhancing the bonding stability between the coating and the substrate to a certain extent.
[0036] Beneficial effects of the present invention:
[0037] The present invention achieves a good balance between strength and toughness of the crankshaft through annealing, quenching and tempering treatments, and is capable of withstanding high loads and alternating stresses, thereby extending the service life of the crankshaft; the wear-resistant and corrosion-resistant coating sprayed on the surface significantly improves the wear resistance of the crankshaft, reduces performance degradation and failures caused by friction and wear, and the wear-resistant and corrosion-resistant coating can also protect the crankshaft from erosion by environmental factors; after multiple steps of polishing treatment, the surface finish of the crankshaft is significantly improved, which is beneficial to reducing friction resistance and improving sealing performance; strict heat treatment process controls the organizational structure of the crankshaft, ensures its dimensional stability, and reduces dimensional changes caused by temperature changes. DETAILED DESCRIPTION
[0038] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0039] Example 1
[0040] The specific process of crankshaft casting is as follows:
[0041] S1: heating the cold heading steel ML20 to 1500°C to make the cold heading steel ML20 molten;
[0042] S2: pouring the molten cold heading steel ML20 into the mold, cooling and solidifying it to obtain a crankshaft blank;
[0043] S3: heating the crankshaft blank to 300° C. and keeping the temperature constant for 2 h, performing annealing treatment, and cooling to room temperature;
[0044] S4: performing surface polishing on the annealed crankshaft blank by using a 500-mesh elastic module at 0.5 MPa for 0.5 h, and then using a 1000-mesh elastic module at 0.5 MPa for 0.5 h;
[0045] S5: heating the polished crankshaft blank to 900°C for quenching treatment, the constant temperature treatment time is 1.5 hours, placing it in cooling water to quickly cool it down, and after cooling, using 70°C nitrogen to purge it until the surface of the crankshaft blank is dry, and the purge flow rate of the nitrogen is 10m / s;
[0046] S6: The quenched crankshaft blank is heated to 200°C for tempering. The constant temperature treatment time is 1 hour. Then nitrogen is evenly sprayed on the surface of the crankshaft blank and slowly cooled to room temperature. The cooling rate is 3°C / min. The spray flow rate of nitrogen is 2.5m 3 / min, pressure is 0.5MPa;
[0047] S7: spraying a layer of wear-resistant and corrosion-resistant coating on the surface of the crankshaft blank after tempering treatment, the spraying parameters are spraying distance 100 mm, spraying rate 60 mm / s, and then drying by laser drying method, the laser drying parameters are laser power 300 W, temperature 50° C., irradiation time 25 min, to obtain the crankshaft;
[0048] The preparation method of the coating used for the wear-resistant and corrosion-resistant coating is as follows:
[0049] S71: Silicon carbide and titanium nitride are mixed in a mass ratio of 1:2, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture A, wherein the particle size of the mixture A obtained by grinding is 200 mesh;
[0050] S72: Heat the polyurethane resin to 170°C to make it molten, add 10wt% of mixture A, 3wt% of cobalt oxide, 1wt% of rhodium oxide, 0.5wt% of polyethylene glycol-1000, and 0.5wt% of diisocyanate, stir at a speed of 200r / min for 1h, cool to room temperature, and obtain the coating used for the wear-resistant and corrosion-resistant coating.
[0051] Example 2
[0052] The specific process of crankshaft casting is as follows:
[0053] S1: heating the cold heading steel ML20 to 1500°C to make the cold heading steel ML20 molten;
[0054] S2: pouring the molten cold heading steel ML20 into the mold, cooling and solidifying it to obtain a crankshaft blank;
[0055] S3: heating the crankshaft blank to 200° C. and keeping the temperature constant for 3 hours, performing annealing treatment, and cooling to room temperature;
[0056] S4: performing surface polishing on the annealed crankshaft blank by using a 500-mesh elastic module at 0.3 MPa for 1 h, and then using a 1000-mesh elastic module at 0.5 MPa for 0.5 h;
[0057] S5: heating the polished crankshaft blank to 830°C for quenching treatment, the constant temperature treatment time is 2 hours, and then placing it in cooling water to quickly cool it down. After cooling, purging it with 70°C nitrogen until the surface of the crankshaft blank is dry, and the purging flow rate of the nitrogen is 10m / s;
[0058] S6: The quenched crankshaft blank is heated to 150°C for tempering. The constant temperature treatment time is 1 to 2 hours. Then nitrogen is evenly sprayed on the surface of the crankshaft blank and slowly cooled to room temperature. The cooling rate is 3°C / min. The spray flow rate of nitrogen is 2.5m3 / min, pressure is 0.5MPa;
[0059] S7: spraying a layer of wear-resistant and corrosion-resistant coating on the surface of the crankshaft blank after tempering treatment, the spraying parameters are spraying distance 100 mm, spraying rate 60 mm / s, and then drying by laser drying method, the laser drying parameters are laser power 260 W, temperature 60° C., irradiation time 30 min, to obtain the crankshaft;
[0060] The preparation method of the coating used for the wear-resistant and corrosion-resistant coating is as follows:
[0061] S71: Silicon carbide and titanium nitride are mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture A, wherein the particle size of the mixture A obtained by grinding is 200 mesh;
[0062] S72: Heat the polyurethane resin to 170°C to make it molten, add 5wt% of mixture A, 2wt% of cobalt oxide, 2wt% of rhodium oxide, 1wt% of polyethylene glycol-800, and 1wt% of triisocyanate, stir at a speed of 150r / min for 2h, cool to room temperature, and obtain the coating used for the wear-resistant and corrosion-resistant coating.
[0063] Example 3
[0064] The specific process of crankshaft casting is as follows:
[0065] S1: heating the cold heading steel ML20 to 1500°C to make the cold heading steel ML20 molten;
[0066] S2: pouring the molten cold heading steel ML20 into the mold, cooling and solidifying it to obtain a crankshaft blank;
[0067] S3: heating the crankshaft blank to 300° C. and keeping the temperature constant for 2 h, performing annealing treatment, and cooling to room temperature;
[0068] S4: performing surface polishing on the annealed crankshaft blank by using a 500-mesh elastic module at 0.5 MPa for 0.5 h, and then using a 1000-mesh elastic module at 0.5 MPa for 0.5 h;
[0069] S5: heating the polished crankshaft blank to 920°C for quenching treatment, the constant temperature treatment time is 1 hour, placing it in cooling water to quickly cool it down, and after cooling, using 70°C nitrogen to purge until the surface of the crankshaft blank is dry, and the purge flow rate of the nitrogen is 10m / s;
[0070] S6: The quenched crankshaft blank is heated to 200°C for tempering. The constant temperature treatment time is 1 hour. Then nitrogen is evenly sprayed on the surface of the crankshaft blank and slowly cooled to room temperature. The cooling rate is 3°C / min. The spray flow rate of nitrogen is 2.5m 3 / min, pressure is 0.5MPa;
[0071] S7: spraying a wear-resistant and corrosion-resistant coating on the surface of the crankshaft blank after the tempering treatment, the spraying parameters are spraying distance 100 mm, spraying rate 60 mm / s, and then drying by laser drying method, the laser drying parameters are laser power 300 W, temperature 50° C., irradiation time 20 min, to obtain the crankshaft;
[0072] The preparation method of the coating used for the wear-resistant and corrosion-resistant coating is as follows:
[0073] S71: Silicon carbide and titanium nitride are mixed in a mass ratio of 1:3, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture A, wherein the particle size of the mixture A obtained by grinding is 200 mesh;
[0074] S72: Heat the polyurethane resin to 170°C to make it molten, add 10wt% of mixture A, 4wt% of cobalt oxide, 2wt% of rhodium oxide, 1wt% of polyethylene glycol-2000, and 1wt% of diisocyanate, stir at a speed of 200r / min for 2h, cool to room temperature, and obtain the coating used for the wear-resistant and corrosion-resistant coating.
[0075] Comparative Example 1
[0076] This comparative example does not perform S3 annealing treatment, and the remaining steps are consistent with Example 1.
[0077] Comparative Example 2
[0078] In this comparative example, S4 surface polishing treatment is not performed, and the remaining steps are consistent with Example 1.
[0079] Comparative Example 3
[0080] In this comparative example, the S7 surface wear-resistant and corrosion-resistant coating is not applied, and the remaining steps are consistent with those in Example 1.
[0081] Comparative Example 4
[0082] In this comparative example, cobalt oxide is not added in the preparation of the wear-resistant and corrosion-resistant coating, and the remaining steps are consistent with those of Example 1.
[0083] Comparative Example 5
[0084] In this comparative example, rhodium oxide is not added in the preparation of the wear-resistant and corrosion-resistant coating, and the remaining steps are consistent with those in Example 1.
[0085] The surface wear resistance of the embodiments and comparative examples was tested according to GB 12444.1-1990;
[0086] The corrosion resistance test was carried out according to ISO 9227:2017. The sample was fixed and the pH value was 3 after adjusting the concentration of 10% sodium chloride with 3% hydrochloric acid. The brine was sprayed on the sample through a spray device. The spray volume was 20mL / s, the spray frequency was 60min / time, each spray was 20s, and after continuous spraying for 72h, the corrosion of the sample was observed.
[0087] The experimental results are summarized in the following table:
[0088] 100 revolutions mass loss / mg Corrosion resistance Example 1 35.4 No corrosion, no bubbles Example 2 35.8 No corrosion, no bubbles Example 3 35.7 No corrosion, no bubbles Comparative Example 1 38.6 No corrosion, no bubbles Comparative Example 2 36.5 No corrosion or bubbles Comparative Example 3 44.8 corrosion Comparative Example 4 40.4 No corrosion or bubbles Comparative Example 5 39.2 No corrosion or bubbles
[0089] Experiments show that annealing and polishing treatments make the crankshaft have better wear resistance and corrosion resistance. The addition of wear-resistant and anti-corrosion coatings further improves the wear resistance and corrosion resistance of the crankshaft.
[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A casting process for a crankshaft for a scroll air-conditioning compressor, characterized in that: The specific process of the crankshaft casting process is as follows: S1: heating the cold heading steel to 1500°C to make the cold heading steel molten; S2: pouring the molten cold heading steel into the mold, cooling and solidifying it to obtain a crankshaft blank; S3: heating the crankshaft blank to 200-300° C. for 2-3 hours, performing annealing treatment, and cooling to room temperature; S4: performing surface polishing on the annealed crankshaft blank by using a 500-mesh elastic module at 0.3-0.5 MPa for 0.5-1 h, and then using a 1000-mesh elastic module at 0.5 MPa for 0.5 h; S5: heating the polished crankshaft blank to 830-920° C. for quenching, with a constant temperature treatment time of 1-2 hours, placing it in cooling water to quickly cool it down, and after cooling, blowing it with 70° C. nitrogen until the surface of the crankshaft blank is dry; S6: heating the quenched crankshaft blank to 150-200° C. for tempering, with a constant temperature treatment time of 1-2 hours, and then evenly spraying nitrogen on the surface of the crankshaft blank and slowly cooling it to room temperature; S7: spraying a layer of wear-resistant and corrosion-resistant coating on the surface of the crankshaft blank after the tempering treatment, and then drying it by a laser drying method to obtain the crankshaft; The preparation method of the coating used for the wear-resistant and corrosion-resistant coating is as follows: S71: Silicon carbide and titanium nitride are mixed in a mass ratio of 1:(1-3), and ground in a ball mill at a rotation speed of 400 r / min for 0.5 h to obtain a mixture A; S72: Heat the polyurethane resin to 170°C to make the polyurethane resin in a molten state, add 5-10wt% of mixture A, 2-4wt% of cobalt oxide, 1-2wt% of rhodium oxide, 0.5-1wt% of dispersant, and 0.5-1wt% of curing agent, stir at a speed of 150-200r / min for 1-2h, cool to room temperature, and obtain the coating used for the wear-resistant and corrosion-resistant coating.
2. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The cold heading steel in S1 is ML20.
3. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The purge flow rate of nitrogen in S5 is 10 m / s.
4. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The spraying flow rate of nitrogen in S6 is 2.5m 3 / min, the pressure is 0.5MPa.
5. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The cooling rate in S6 is 3°C / min.
6. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The spraying parameters in S7 are spraying distance 100 mm and spraying rate 60 mm / s.
7. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The parameters of the laser drying in S7 are: laser power 260-300 W, temperature 50-60° C., and irradiation time 20-30 min.
8. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The particle size of the mixture A obtained by grinding in S71 is 200 mesh.
9. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The dispersant in the S72 is polyethylene glycol, and the number average molecular weight is 800-2000.
10. The casting process of a crankshaft for a scroll air-conditioning compressor according to claim 1, characterized in that: The curing agent in S72 is one of diisocyanate and triisocyanate.
